2009
DOI: 10.1016/j.limno.2008.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Biometric analysis of lacustrine and riverine populations of Palemonetes antennarius (H. Milne-Edwards, 1837) (Crustacea, Decapoda, Palaemonidae) from north-western Greece

Abstract: Comparative study of morphometric measurements was undertaken on populations of Palaemonetes antennarius from two freshwater habitat zones (lacustrine pelagic and lacustrine littoral) and from the fluvial littoral habitat zone of three estuaries of north-western Greece. Multivariate statistical analyses (principal component analysis and discriminant function analysis) revealed clear morphometric differences between sexes and sampling sites. The observed differences are expressed mainly thought the measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
(27 reference statements)
0
22
0
2
Order By: Relevance
“…In similar studies, the strong discriminating power of morphometric variables has been recognized (Waldman et al, 1997;Murta, 2000;Garcia-Davila et al, 2005;Ferrito et al, 2007;Anastasiadou and Leonardos, 2008;Anastasiadou et al, 2009). This has shown that the morphometric characters used in this study have an application in taxonomy and may be used as indices to measure morphometric variation among Mugil groups.…”
Section: Discussionmentioning
confidence: 76%
“…In similar studies, the strong discriminating power of morphometric variables has been recognized (Waldman et al, 1997;Murta, 2000;Garcia-Davila et al, 2005;Ferrito et al, 2007;Anastasiadou and Leonardos, 2008;Anastasiadou et al, 2009). This has shown that the morphometric characters used in this study have an application in taxonomy and may be used as indices to measure morphometric variation among Mugil groups.…”
Section: Discussionmentioning
confidence: 76%
“…Apesar da diferença significativa de tamanho entre machos e fêmeas, ambos atingem a maturidade sexual morfológica com aproximadamente 32,5 mm de largura da carapaça (Reigada & Negreiros-Fransozo, 1999). O tamanho corpóreo maior de fêmeas pode ser explicado, em parte, por fatores relacionados à variação populacional (status nutricional e disponibilidade de alimento) ou a metodologia de coleta empregada, que pode ter selecionado fêmeas maiores que machos (Anastasiadou et al, 2009).…”
Section: Discussionunclassified
“…The shrimp P. antennarius is an euryhaline species, inhabiting freshwaters and estuarine habitats (Parry & Potts 1965;DallaVia 1983DallaVia , 1986Gottstein Matočec & Kerovec2002;Gottstein Matočec et al 2006;Anastasiadou et al 2009). Its well established population in the lake can possibly be attributed to a succession of events.…”
Section: Discussionmentioning
confidence: 99%
“…These two major families are represented up today by five species in Greek freshwater ecosystems: the freshwater shrimps Atyaephyra acheronensis Christodoulou et al, 2012, A. stankoi Karaman, 1972, A. strymonensis Christodoulou et al, 2012and A. thyamisensis Christodoulou et al, 2012 and the grass shrimp Palaemonetes antennarius (H. Milne-Edwards, 1837). The only published information on the freshwater Greek shrimp fauna is focused on zoogeography, taxonomy, morphometry and karyological analysis (Anastasiadou et al 2004(Anastasiadou et al , 2009Anastasiadou & Leonardos 2008, 2010García Muńoz et al 2009;Christodoulou et al 2012), while bionomic studies are lacking at all. But, as it has been recorded in previous studies, the freshwater shrimps play a crucial role in ecosystems, occurring in a variety of habitats (De Grave et al 2008) and transferring energy from lower levels of the trophic chain (detritus, phytoplankton and riparian vegetation) to higher ones (carnivorous fishes) (Meurisse-Genin et al 1985;Fidalgo 1989;García-Berthou & Moreno-Amich 2000;Fidalgo & Gerhardt 2002;Duarte et al 2012).…”
Section: Introductionmentioning
confidence: 99%